A Becn1 mutation mediates hyperactive autophagic sequestration of amyloid oligomers and improved cognition in Alzheimer's disease. - Altea Rocchi; Soh Yamamoto; Tabitha Ting; Yuying Fan; Katherine Sadleir; Yigang Wang; Weiran Zhang; Sui Huang; Beth Levine; Robert Vassar; Congcong He (PLoS Genetics)
Impairment of the autophagy pathway has been observed during the pathogenesis of Alzheimer's disease (AD), a neurodegenerative disorder characterized by abnormal deposition of extracellular and intracellular amyloid β (Aβ) peptides. Yet the role of autophagy in Aβ production and AD progression is complex. To study whether increased basal autophagy plays a beneficial role in Aβ clearance and cognitive improvement, we developed a novel genetic model to hyperactivate autophagy in vivo. We found that knock-in of a point mutation F121A in the essential autophagy gene Beclin 1/Becn1 in mice significantly reduces the interaction of BECN1 with its inhibitor BCL2, and thus leads to constitutively active autophagy even under non-autophagy-inducing conditions in multiple tissues, including brain. Becn1F121A-mediated autophagy hyperactivation significantly decreases amyloid accumulation, prevents cognitive decline, and restores survival in AD mouse models. Using an immunoisolation method, we found biochemically that Aβ oligomers are autophagic substrates and sequestered inside autophagosomes in the brain of autophagy-hyperactive AD mice. In addition to genetic activation of autophagy by Becn1 gain-of-function, we also found that ML246, a small-molecule autophagy inducer, as well as voluntary exercise, a physiological autophagy inducer, exert similar Becn1-dependent protective effects on Aβ removal and memory in AD mice. Taken together, these results demonstrate that genetically disrupting BECN1-BCL2 binding hyperactivates autophagy in vivo, which sequestrates amyloid oligomers and prevents AD progression. The study establishes new approaches to activate autophagy in the brain, and reveals the important function of Becn1-mediated autophagy hyperactivation in the prevention of AD.